Epicardial adipose tissue in patients with heart failure - Dösch, Christina; Haghi, Dariusch; Flüchter, Stephan; Süselbeck, Tim; Schönberg, Stefan; Michaely, Henrik J. M.; Borggrefe, Martin; Papavassiliu, Theano (Journal of cardiovascular magnetic resonance, 2010)
Purpose: The aim of this study was to evaluate the extent of epicardial adipose tissue (EAT) and its relationship with left ventricular (LV) parameters assessed by cardiovascular magnetic resonance (CMR) in patients with congestive heart failure (CHF) and healthy controls. - Background: EAT is the true visceral fat deposited around the heart which generates various bioactive molecules. Previous studies found that EAT is related to left ventricular mass (LVM) in healthy subjects. Further studies showed a constant EAT to myocardial mass ratio in normal, ischemic and hypertrophied hearts. - Methods: CMR was performed in 66 patients with CHF due to ischemic cardiomyopathy (ICM), or dilated cardiomyopathy (DCM) and 32 healthy controls. Ventricular volumes, dimensions and LV function were assessed. The amount of EAT was determined volumetrically and expressed as mass indexed to body surface area. Additionally, the EAT/LVM and the EAT/left ventricular remodelling index (LVRI) ratios were calculated. - Results: Patients with CHF had less indexed EAT mass than controls (22 ± 5 g/m2 versus 34 ± 4 g/m2, p < 0.0001). In the subgroup analysis there were no significant differences in indexed EAT mass between patients with ICM and DCM (21 ± 4 g/m2 versus 23 ± 6 g/m2, p = 0.14). Linear regression analysis showed that with increasing LV end-diastolic diameter (LV-EDD) (r = 0.42, p = 0.0004) and LV end-diastolic mass (LV-EDM) (r = 0.59, p < 0.0001), there was a significantly increased amount of EAT in patients with CHF. However, the ratio of EAT mass/LV-EDM was significantly reduced in patients with CHF compared to healthy controls (0.54 ± 0.1 versus 0.21 ± 0.1, p < 0.0001). In CHF patients higher indexed EAT/LVRI-ratios in CHF patients correlated best with a reduced LV-EF (r = 0.49, p < 0.0001). - Conclusion: Patients with CHF revealed significantly reduced amounts of EAT. An increase in LVM is significantly related to an increase in EAT in both patients with CHF and controls. However, different from previous reports the EAT/LVEDM-ratio in patients with CHF was significantly reduced compared to healthy controls. Furthermore, the LV function correlated best with the indexed EAT/LVRI ratio in CHF patients. Metabolic abnormalities and/or anatomic alterations due to disturbed cardiac function and geometry seem to play a key role and are a possible explanation for these findings.
Gesehen am 15.05.2023